2006
DOI: 10.1016/j.jtherbio.2006.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Absence of a causal relationship between environmental and body temperature in dairy cows (Bos taurus) under moderate climatic conditions

Abstract: Abstract1. Continuous body temperature records from dairy cows for 46 days of summer and contemporary data for climate temperature humidity index (THI) were analysed, 2. A large component of the body temperature data was not explained by changes in THI.3. Outside a normal range of values (above 72 for THI and 39.05 o C for body temperature), there was evidence of a causal relationship with a time delay of about 120 minutes.4. Both variables had a prominent circadian component, but these were more likely to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
1
18
1
2
Order By: Relevance
“…Base de regras da taxa de detecção de estro de vacas leiteiras em função do índice de temperatura e umidade (ITU), período após último cio (PAUC) e número de comportamentos observados (NCO) Na simulação proposta, a base de regras foi ajustada para valores de entrada ideais. Desta forma, o índice de temperatura e umidade (ITU) assumiu valor igual a 70, segundo sugestão de VERWOERD et al (2006) e MARTELLO (2006. No caso de vacas que não sofreram estresse térmico ou qualquer outro tipo de disfunção, segundo VANZIN (2006) o dia mais provável para que este animal entre no cio é 21º dia.…”
Section: Resultsunclassified
“…Base de regras da taxa de detecção de estro de vacas leiteiras em função do índice de temperatura e umidade (ITU), período após último cio (PAUC) e número de comportamentos observados (NCO) Na simulação proposta, a base de regras foi ajustada para valores de entrada ideais. Desta forma, o índice de temperatura e umidade (ITU) assumiu valor igual a 70, segundo sugestão de VERWOERD et al (2006) e MARTELLO (2006. No caso de vacas que não sofreram estresse térmico ou qualquer outro tipo de disfunção, segundo VANZIN (2006) o dia mais provável para que este animal entre no cio é 21º dia.…”
Section: Resultsunclassified
“…Robertshaw (1985) indicated that controlling and maintaining the temperature of the central nervous system, particularly the brain, is the most important function of the body, as the brain is highly susceptible to changes in temperature. In a study conducted by Verwoerd et al (2006), the authors showed that cattle were able to isolate their body temperature from the thermal environment during moderate temperatures, however when conditions become hot cattle are no longer able to cope with increasing ambient conditions. Furthermore Spiers et al (2004) indicated that rectal temperature of beef cattle increased within 24 hours after the introduction of thermal stress.…”
Section: Core Body Temperaturementioning
confidence: 99%
“…digestion and locomotion, also result in an increase in core body temperature and therefore the diurnal pattern exhibited. Verwoerd et al (2006) showed that cattle are able to isolate their body temperature from the thermal environment during moderate temperatures. When conditions become hot, however, cattle are no longer able to cope with increasing ambient conditions.…”
Section: New Technologies In the Measurement Of Body Temperaturementioning
confidence: 99%
“…Apenas correlações fracas ou não significativas foram verificadas para os hormônios IGF-I e cortisol, entre eles e com as variáveis fisiológicas e ambientais. (FUQUAY, 1981;JONHSON, 1980;MAYER et al, 1999;VERWOERD et al, 2006;WEST, 1999). Entretanto, esses limites máximos podem variar devido a inúmeros fatores como grau de aclimatação do animal, tempo de exposição ao estresse, prenhez e nível de produção.…”
Section: Resultsunclassified